2013
DOI: 10.1002/kin.20765
|View full text |Cite
|
Sign up to set email alerts
|

Rate Coefficients for the Gas‐Phase Reactions of Chlorine Atoms with Cyclic Ethers at 298 K

Abstract: Rate coefficients of reactions of Cl atoms with cyclic ethers, tetrahydropyran (THP), tetrahydrofuran (THF), and dihydrofurans (2,5-DHF and 2,3-DHF) have been measured at 298 K using a relative rate method. The relative rate ratios for THP and THF are 0.80 ± 0.05 and 0.80 ± 0.08, respectively, with n-hexane as the reference molecule. The relative rate ratios for THF and 2,5-DHF with n-pentane as the reference molecule are 0.95 ± 0.07 and 1.73 ± 0.06, respectively, and for 2,5-DHF with 1-butene as reference is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
2
14
2
Order By: Relevance
“…5,6 The kinetics of the reaction of THF with chlorine atoms, for which the overall rate constant for H atoms abstraction, is designated as k H THF + Cl → Product (1) was the subject of two experimental studies. 7,8 Giri and Roscoe 7 studied the reaction of Cl + THF in the temperature range of 298.4-362.3 K and in the pressure range of 403-760 Torr. The authors showed that the overall rate constant for this reaction is temperature and pressure independent, with the average value of the overall rate constant of (2.71 ± 0.34) × 10 −10 cm 3 molecule −1 s −1 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…5,6 The kinetics of the reaction of THF with chlorine atoms, for which the overall rate constant for H atoms abstraction, is designated as k H THF + Cl → Product (1) was the subject of two experimental studies. 7,8 Giri and Roscoe 7 studied the reaction of Cl + THF in the temperature range of 298.4-362.3 K and in the pressure range of 403-760 Torr. The authors showed that the overall rate constant for this reaction is temperature and pressure independent, with the average value of the overall rate constant of (2.71 ± 0.34) × 10 −10 cm 3 molecule −1 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…They determined that the average value of the overall rate constant equaled to (2.50 ± 0.39) ×10 −10 cm 3 molecule −1 s −1 . 8 In this paper, we present the experimental kinetic studies of the Cl reaction with THF in the temperature range of 298-547 K, using the relative rate method. The kinetic studies of fully deuterated tetrahydrofuran TDF (where "TDF" denotes fully deuterated THF) with atomic chlorine have also been performed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations